2021
DOI: 10.26714/hnca.v1i1.8263
|View full text |Cite
|
Sign up to set email alerts
|

Penurunan Tingkat Kecemasan pada Pasien Pre Operasi Sectio Caesarea dengan Terapi Murotal dan Edukasi Pre Operasi

Abstract: Tindakan operasi sectio caesareadilakukan untuk mencegah kematian janin dan ibu karena adanya suatu komplikasi yang akan terjadi kemudian bila persalinan dilakukan secara pervaginam, sehingga dapat menyebabkan kecemasan pada pasien yang dapat menghambat proses penyembuhan post operasi. Berbagai macam cara dilakukan untuk mengatasi kecemasan pre operasi, diantaranya adalah terapi Murotal dan edukasi pre operasi.studi kasus ini bertujuan  untuk mengetahui penurunan tingkat kecemasan pada pasien sectio caesareade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
3
0
5
Order By: Relevance
“…And it can be concluded that there is a difference in the average anxiety index score before and after deep breathing relaxation therapy in patients with pre-abdominal surgery, with a p-value of (0.000) [18]. The same study was also conducted by Fatmawati (2016) with the title The Effect of Progressive Relaxation and Lavender Aromatherapy on Reducing Anxiety in Preoperative Patients. The research data were analyzed using the paired t-test, based on the results of the data it was known that there was a difference in the average pre-test and post-test anxiety with p-value = 0.001 (p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…And it can be concluded that there is a difference in the average anxiety index score before and after deep breathing relaxation therapy in patients with pre-abdominal surgery, with a p-value of (0.000) [18]. The same study was also conducted by Fatmawati (2016) with the title The Effect of Progressive Relaxation and Lavender Aromatherapy on Reducing Anxiety in Preoperative Patients. The research data were analyzed using the paired t-test, based on the results of the data it was known that there was a difference in the average pre-test and post-test anxiety with p-value = 0.001 (p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Anxiety is an unpleasant feeling as a manifestation of various emotional feelings that occur when individuals are experiencing emotional stress (frustration) and inner conflict (conflict). In adults, anxiety is influenced by several factors, one of which is age, gender, type of disease, individual coping and level of knowledge or lack of knowledge (Fatmawati, 2021). The results of table 2 analysis show that after listening to Murottal Al-Quran most of the respondents' anxiety is in the mild anxiety category of 61 (64.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Asuhan pada pasien preoperasi sectio caesarea dengan mendengarkan 30menit terbukti secara efektif menurunkan kecemasan sebelum pelaksanaan operasi sectio secarea. (Fatmawati & Pawestri, 2021)…”
Section: Menurunkan Kecemasan Pada Pasien Preoperasi Sectio Caesareaunclassified